2023
DOI: 10.1007/s00018-023-04936-z
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and dynamics of the proton shuttle of carbonic anhydrase II

Heiner N. Raum,
Suzanne Zoë Fisher,
Ulrich Weininger

Abstract: Human carbonic anhydrase II catalyzes the reversible reaction of carbon dioxide and water to form bicarbonate and a proton. His64-mediated proton shuttling between the active site and the bulk solvent is rate limiting. Here we investigate the protonation behavior of His64 as well as its structural and dynamic features in a pH dependent way. We derive two pKa values for His64, 6.25 and 7.60, that we were able to assign to its inward and outward conformation. Furthermore, we show that His64 exists in both confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The mechanism outlined above is presented in Figure b with additional details added from a large body of simulation studies at neutral pH. , Two major dynamical reorganization processes have been found to be crucial in initiating the actual proton transfer across the active site: (i) rapid fluctuations of the coordination number of zinc ion between 4 and 5 and (ii) fast rotation of His-64 side chain between its in and out orientations. The fast kinetics associated with His-64 side chain rotation has recently been confirmed by nuclear magnetic resonance (NMR) studies . Subsequently, reorganization of water molecules at the active site is found to facilitate transfer of the proton fluctuating between its Eigen and Zundel forms ,,, These dynamical fluctuations have been shown to be necessary to reproduce the experimental value of k cat (∼0.8–1.25 × 10 6 μs –1 ) .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The mechanism outlined above is presented in Figure b with additional details added from a large body of simulation studies at neutral pH. , Two major dynamical reorganization processes have been found to be crucial in initiating the actual proton transfer across the active site: (i) rapid fluctuations of the coordination number of zinc ion between 4 and 5 and (ii) fast rotation of His-64 side chain between its in and out orientations. The fast kinetics associated with His-64 side chain rotation has recently been confirmed by nuclear magnetic resonance (NMR) studies . Subsequently, reorganization of water molecules at the active site is found to facilitate transfer of the proton fluctuating between its Eigen and Zundel forms ,,, These dynamical fluctuations have been shown to be necessary to reproduce the experimental value of k cat (∼0.8–1.25 × 10 6 μs –1 ) .…”
Section: Introductionmentioning
confidence: 85%
“…Earlier experimental observations implied a pK a of 7.1 for His-64 in HCA II. 69 In a more recent study, 43 NMR spectroscopy within the pH range 5−10 reported for the first time two distinct pK a values of 6.25 and 7.60 associated with its in and out conformations, respectively. Our estimates, despite a nonequilibrium sampling reported at pH 5 and 6, corroborate well to the conformationdependent values of pK a as obtained from the NMR titration of His-64 side chain in HCA II.…”
Section: Dynamics Of Coupled Charge and Orientation Fluctuation Of Hi...mentioning
confidence: 97%
See 1 more Smart Citation
“…These features make histidine the chemically most versatile amino acid, and it is often engaged in catalysis. 4,5 In fact, histidine has many different functions: it can act as a nucleophile and as an acid/base catalyst, 6,7 e.g., in catalytic triads, 8,9 as a proton shuttle, 10,11 as a hydrogen bond donor and acceptor, 12,13 and it can coordinate metal ions. 14 Hydrogen bonding involving histidine is of particular interest in the context of protein structure.…”
Section: ■ Introductionmentioning
confidence: 99%